2014
DOI: 10.1093/fampra/cmu040
|View full text |Cite
|
Sign up to set email alerts
|

Coping with colorectal cancer: a qualitative exploration with patients and their family members

Abstract: Findings from this study have implications for understanding how families blend emotion-based and problem-focused coping strategies in the face of a CRC diagnosis. Further developing evidence-based interventions that target coping and well-being in cancer patients and extending them to family members is necessary and holds great promise for providers who care for patients with familial cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
3
32
0
1
Order By: Relevance
“…This is not unique, as Papastavrou, Charalambous, & Tsangari (), in a study conducted in Cyprus, found finding solace in faith was one of the three most commonly used strategies family members use to cope with the demands of their care role. Asiedu, Eustace, Eton, and Breitkopf () support this finding by providing evidence that family members use religion to cope with cancer, as they believe a higher power is in control and that their faith allowed them to move forward. It was interesting to find “wishful thinking” and denial were only initially used by family members in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…This is not unique, as Papastavrou, Charalambous, & Tsangari (), in a study conducted in Cyprus, found finding solace in faith was one of the three most commonly used strategies family members use to cope with the demands of their care role. Asiedu, Eustace, Eton, and Breitkopf () support this finding by providing evidence that family members use religion to cope with cancer, as they believe a higher power is in control and that their faith allowed them to move forward. It was interesting to find “wishful thinking” and denial were only initially used by family members in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…Cancer survivors felt out of control and not able to contain their worry and negative thoughts about their possible death, focusing on the worst-case scenarios (Asiedu et al, 2014).…”
Section: Transformed Selfmentioning
confidence: 99%
“…[20] Abelson et al . [27] reported one of the few studies that explored the coping strategies of CRC patients alone, as previous studies explored these strategies from families' and caregivers' perspectives and focused on general malignancies. [2829] However, Abelson et al .…”
Section: Discussionmentioning
confidence: 99%